Environment Management of the Iraq Marshlands : water Quality Management united Nations Environment programme 2005 - جاسم جبر انتظار; نعيم جاسم شروق (Al-Adab Journal, 2018)
Penetrate the eastern border of Iraq with Iran, small rivers and streams for many water taking place mostly from Iranian territory has been going with the boundary line, cut to pour in the end, inside Iraq, and that a portion of these rivers and valleys around the problems did not occur in the past and this mostly located in the northern region which is the same slope stems from being a very mountainous area with steep slopes and features quickly to neighbors near the headwaters, and that the Iranian authorities are having difficulty controlling them. In the southern parts, and also Snodha in our research this on the rivers Karkheh and Karun Shatt al-Arab and other Alanharalta become one of the most important rivers which suffer from water problems with Iran, as it acted according to the whims and interests, despite the violation of her actions the provisions of the agreements provided for the Iraqi territory stakes Bucking the good-neighborly relations, claiming that these conventions were held and approved at a time when Iran was in a weak position, and that it has the right to revocation and repudiated.